Deactualization while Presenting the Fragments of Collective Memory in German and Russian Mass Media - L. N. Rebrina (Научный диалог, 2017)
The results of the analysis conducted in the framework of a comparative linguistic study of patterns of collective memory reactualization in the media in Germany and Russia are presented. Ethnocultural specificity of the discursive practices of memory remains understudied. Collective memory is understood as discursive, socially constructed through relevant strategies phenomenon, as a symbolic reconstruction of the past that meets modern needs. Media as a tool of social control are effective means of manifestation of the collective memory. Object of research are the features of deactualizing presentation of the past in the media of the two countries, displacing communicative focus from specific events and counteracting the emotional involvement of the recipient and the formation of value attitude to the past. The relevance of this strategy is determined by the coexistence of competing pictures of the past and memory conflicts. Analyzed communicative interaction is characterized by the subject-object relation between the addresser and the addressee. According to the results of research it is concluded about the regularity of the implementation of the media installation for the mass desensitization of the recipient in relation to past events. The smaller relevance of the described strategy to the Russian media, the similarity of the repertoire of tactics of displacement of communicative focus from the evaluation of the fragments of a collective past in Russian and German media are mentioned. The most and least frequent tactics of deactualizing the presentation of the past are identified.